2008
DOI: 10.1097/mlg.0b013e3181781791
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Results of Radiotherapy for T1a and T1bN0M0 Glottic Carcinoma

Abstract: Radiotherapy with a total dose of 67 to 70 Gy seemed to be required for local control in T1b glottic carcinoma. No significant benefit of total radiation dose > 64 Gy was shown in the analysis of T1a glottic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…In our analysis, factors that adversely affected LC were T stage, overall treatment time exceeding 41 days, and poorly differentiated histology. Others have reported that smaller fraction size, subglottic extension, treatment delays/interruptions, age, smaller field sizes, lower total dose, gender, stage, higher beam energy, anterior commissure involvement, pretreatment hemoglobin levels, and impaired vocal cord mobility adversely affect LC (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 96%
“…In our analysis, factors that adversely affected LC were T stage, overall treatment time exceeding 41 days, and poorly differentiated histology. Others have reported that smaller fraction size, subglottic extension, treatment delays/interruptions, age, smaller field sizes, lower total dose, gender, stage, higher beam energy, anterior commissure involvement, pretreatment hemoglobin levels, and impaired vocal cord mobility adversely affect LC (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 96%
“…There are many cases of T1. Nomiya et al [12] reported that the 5-year survival rate was 85% and the 10-year survival rate was 73% in 115 patients with T1a laryngeal cancer, and 89% and 85%, respectively, in 48 patients with T1b. The larynx preservation rate was 92% at 5 years and 85% at 10 years in T1a patients and 85% and 76%, respectively, in T1b patients.…”
Section: Discussionmentioning
confidence: 97%
“…8 In the literature, local control of T1 glottic lesions reaches over 90%, varying according to involvement of one or both vocal folds. 9,10 Thus, local control is decreased in lesions that involve the anterior commissure (92.3% 5-year disease-free survival rate) compared to lesions only in one vocal fold (85% 5-year disease-free survival rate).…”
Section: Discussionmentioning
confidence: 99%